ANALISIS RISIKO KETERLAMBATAN PROYEK TAHAP PRA KONSTRUKSI (STUDI KASUS JEMBATAN BENGKALIS RIAU) - Yuli Rahman; Ari Sandhyavitri; Alex Kurniawandy (LPPM Universitas Abdurrab, 2026)
The pre-construction stage is a critical phase that frequently causes delays in large-scale infrastructure projects. This study aims to identify and analyze the delay risks during the pre-construction stage of the Bengkalis Bridge, which connects Bengkalis Island to the mainland of Sumatra. The methodology employed is a mixed-methods approach, utilizing questionnaire surveys distributed to 78 respondents comprising government officials, private sector representatives, and experts/academics to determine the Relative Importance Index (RII) rankings. The quantitative data were subsequently validated through in-depth interviews with relevant ministries/agencies and infrastructure public policy experts. The findings identified 33 risk variables divided into 6 categories, with 17 variables classified as dominant risks. The primary risk groups encompass funding availability, political and regulatory uncertainties, land acquisition constraints, and uncontrollable events (force majeure/unforeseen conditions). Risk mitigation approaches must be executed comprehensively rather than partially. The formulation of an integrated risk management strategy includes efforts to designate the development as a National Strategic Project (PSN), implement land acquisition regulations (Government Regulation No. 19/2021 in conjunction with Government Regulation No. 39/2023), and optimize the national budgeting mechanism